2015
DOI: 10.14202/vetworld.2015.1300-1304
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and epidemiology of Salmonella enterica serovar Gallinarum from poultry in some parts of Haryana, India

Abstract: Aim: The present study was investigated to ascertain the epidemiological status of fowl typhoid (FT) in broilers in some parts of Haryana during January 2011 to December 2013. Materials and Methods:To elucidate the epidemiological status of FT in broiler chickens for the 3 years (2011)(2012)(2013) and to study the prevalence of various Salmonella serovars in poultry on the basis of culture characteristics, biochemical features, serotyping, and their antibiogram profile from some parts of Haryana (India). Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…We found that the prevalence of Salmonella enterica was higher in isolates from RMS samples, followed by hatcheries and CBF. Similar finding was reported in China [ 38 ], Egypt [ 39 ], and Haryana, India [ 40 ].…”
Section: Discussionsupporting
confidence: 88%
“…We found that the prevalence of Salmonella enterica was higher in isolates from RMS samples, followed by hatcheries and CBF. Similar finding was reported in China [ 38 ], Egypt [ 39 ], and Haryana, India [ 40 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our research results correlate with the reports of other scientists (Basu et al, 1975;Arora et al, 2015), who recorded 89.5% of poultry deaths in the Indian states of Karnataka, Maharashtra, and Tamil Nadu caused by microorganisms of the species S. pullorum. Clinical manifestations of the disease, such as depression, anorexia, greenish-yellow diarrhea, and nervous phenomena in the form of the head tilt were detected in 2001 during the salmonellosis outbreak in the state of Tripura in eastern India.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, in the β-lactam group, 100% resistance to cefotaxime was found, similar to the percentages reported in S. Infantis strains in Ecuador (87.5-99%) and Egypt, Korea, and Serbia (78.9-100%) [31,[46][47][48]. In S. Gallinarum isolates, resistance up to 85% was reported in India [49]. This resistance may be associated with cross-resistance caused by using other cephalosporins in poultry farming, such as ceftiofur [50,51], which is an antibiotic to which all strains in this study were also resistant.…”
Section: Discussionsupporting
confidence: 81%